Z maloměsta okresní město: (urbanistický vývoj Žďáru nad Sázavou: etnologický pohled) - Porsch, Josef (Lidé města, 2004)
This study is part of a more extensive research programme taking place in Žďár nad Sázavou. The aim is to try to capture urbanistic development of the town with some ethnographic incentives. One outcome of the research aims to map the everyday way of life of people during socialism before it is lost. The locale of Žďár nad Sázavou serves as a regional example. In order to thoroughly understand the processes that have been taking place in the town we have to be aware of its urbanistic developoment. Housing, infrastructure and social background are the foundation stones of most of the social activities. During the existence of the Žďas factories, the town of Žďár nad Sázavou has changed beyond recognition. Officially it is said that the last four decades mean more to the town than the whole of previous centuries. Thanks to controlled industrialisation and monitored town planning, the difference between town and countryside has been purposefully erased. The former pour small town turned into a modern one: where, under socialism a lot of fair work had gone on; a town of new houses, a town of TV´s and all the modem conveniences. Such is the life created by the socialist society. Yet we can see some relics that survived the town's mushroom growth (for example, a splendid train station which does not have an automatic train departure board, the notices are still inserted manually). The socialist development has also determined Žďár´s future outlooks. Even here, 'the cards are dealť and it is up to the residents and their representatives to deal with their heritage, a heritage that is neither bad, nor good.